2008
DOI: 10.1002/gepi.20307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of approaches for machine‐learning optimization of neural networks for detecting gene‐gene interactions in genetic epidemiology

Abstract: The detection of genotypes that predict common, complex disease is a challenge for human geneticists. The phenomenon of epistasis, or gene-gene interactions, is particularly problematic for traditional statistical techniques. Additionally, the explosion of genetic information makes exhaustive searches of multilocus combinations computationally infeasible. To address these challenges, neural networks (NN), a pattern recognition method, have been used. One limitation of the NN approach is that its success is dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 38 publications
0
88
0
Order By: Relevance
“…However, even if a linear model holds at least locally, a standard fixed effects ANOVA of a highly dimensional, multifactorial system is not feasible, because one ' runs out ' of degrees of freedom (df) (Gianola et al, 2006). Nevertheless, methodologies for dealing with complex epistatic systems are becoming available and these include, for example, machine learning, regularized neural networks (Lee, 2004), neural networks optimized with grammatical evolution computations (Motsinger-Reif et al, 2008) and non-parametric regression (e.g. Gianola et al, 2006 ;Gianola & van Kaam, 2008).…”
Section: Confronting Complexitymentioning
confidence: 98%
“…However, even if a linear model holds at least locally, a standard fixed effects ANOVA of a highly dimensional, multifactorial system is not feasible, because one ' runs out ' of degrees of freedom (df) (Gianola et al, 2006). Nevertheless, methodologies for dealing with complex epistatic systems are becoming available and these include, for example, machine learning, regularized neural networks (Lee, 2004), neural networks optimized with grammatical evolution computations (Motsinger-Reif et al, 2008) and non-parametric regression (e.g. Gianola et al, 2006 ;Gianola & van Kaam, 2008).…”
Section: Confronting Complexitymentioning
confidence: 98%
“…Potential avenues for addressing this problem include nonparametric regression (e.g., Gianola et al 2006a, b;Gianola and van Kaam 2008), methods based on regularized neural networks (Lee 2004) or neural networks optimized with grammatical evolution computations (Motsinger-Reif et al 2008). For example, Gianola et al (2006a, b) and Gianola and van Kaam (2008) suggested using reproducing kernel Hilbert spaces (RKHS) regression, where dense molecular information enters into a positive-definite kernel (incidence) matrix whose dimension is equal to the number of individuals with genotype information.…”
Section: Other Forms Of Dealing With Complexitymentioning
confidence: 99%
“…The steps of GENN have been previously described in detail [1]. For the purposes of the current study, an option was added to the configuration file to specify the fitness function used: classification error (CE) or balanced error (BE).…”
Section: Grammatical Evolution Neural Networkmentioning
confidence: 99%
“…Grammatical Evolution Neural Networks (GENN) uses grammatical evolution to evolve neural networks to detect gene-gene interactions in studies of complex human diseases [1].…”
Section: Introductionmentioning
confidence: 99%